Efficiency of Near-Infrared Technology in the Clinical Detection of Carious Lesions: A Systematic Review - Elsawaf, Ahmed Essam; Deri, Abdulsalam Youssef Al; Armanious, Patrick Samih; Khasawneh, Abdallah Mahmoud; AlKhaja, Ahmed Mahmood; Yasin, Ahmad Ribhi; Al-Rawi, Natheer Hashim; Kawas, Sausan Al; Shetty, Shishir Ram (European Journal of Dentistry, 2023)
The field of dentistry has seen various technological advances regarding caries detection, some lesions still prove to be difficult to detect. A reasonably new detection method, near-infrared (NIR), has shown good results in caries detection. This systematic review aims to compare NIR with conventional methods in terms of caries detection. Online databases (PubMed, Scopus, ScienceDirect, EBSCO, and ProQuest) were used for the literature search. The search was performed from January 2015 till December-2020. A total of 770 articles were selected, of that 17 articles qualified for the final analysis as per Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The articles were assessed according to a modified Critical Appraisal Skills Programme checklist, and then synthesis of the review started. The inclusion criteria were clinical trials done in vivo on teeth with active caries of vital or nonvital teeth. This review excluded nonpeer reviewed articles, case reports, case series, opinions, abstracts, non-English written articles, studies of subjects with arrested caries, or teeth with developmental defects of tooth structure and teeth having environmental defects of tooth structure, as well as in-vitro studies. The review compared near-infrared technology with radiography, visual inspection, and laser fluorescence in terms of caries detection, sensitivity, specificity, and accuracy. The sensitivity of NIR ranged from 99.1 to 29.1%. Studies showed that NIR exhibited higher sensitivity for occlusal enamel and dentin caries. The specificity of NIR ranged from 94.1 to 20.0%. In enamel and dentinal occlusal caries, NIR demonstrated lower specificity than that of radiograph. The specificity of NIR in early proximal caries was low. Accuracy was determined in 5 out of 17 studies where the values ranged from 97.1 to 29.1%. The accuracy of NIR was the highest for dentinal occlusal caries. NIR shows promising evidence as an adjunct in caries examination due to its high sensitivity and specificity; however, more studies are required to determine its full potential in different situations.
Keywords: dental caries; near-infrared; radiographs; efficiency; detection; visual inspection; laser fluorescence; transillumination